Stress Distribution Behavior in Single-Lap Adhesively Bonded Beams - He, X.; Wang, Y. (Проблемы прочности, 2014)
In the present work, the stress distribution along the total single-lap adhesively bonded beam has been investigated using the 3D finite element (FE) method. Specifically, FE solutions of the stress distributions in the bonded section have been obtained for four typical characteristics of adhesives. С помощью трехмерного метода конечных элементов исследовалось распределение напряжений вдоль неразрезных балок, адгезионно соединенных внахлестку За допомогою тривимірного методу скінченних елементів досліджено розподіл напружень уздовж нерозрізних балок, адгезійно з'єднаних внапуск.